Biodiversity Index value of benthic invertebrates' community in relation with variation of some environmental properties in Rivers Tigris and Diyala within Baghdad city. (Baghdad Science Journal, 2025)
This study was carried out to determine the effects of some environmental variables on biodiversity index value of benthic invertebrates' community in samples that collected monthly from two adjacent sites nearby the confluence of Tigris and Diyala rivers within Baghdad city that’s from November 2007 - October 2008.Results showed differences in chemical and physical characteristics for each river. Where the annual averages of these characteristics in Rivers Tigris and Diyala respectively for: water temperature (20, 19) Cº, pH (8, 8), Dissolved oxygen DO(8,4 ) mg/l , EC(1152,2979)µc/cm , Turbidity (28,74) NTU, Total Hardness of CaCO3 (485,823)mg/l, and finally NO3 (4,6)mg/l.Concerning the biological groups, included types of Insects, Mollusks, Oligochaeta and finally Crustacea. The results revealed that the highest population density of insects in Rive Tigris was (31493.28) individual / m2, mollusks were (23177.64) individual / m2, Oligochaeta (10774.95) individual / m2, Crustacea (176.92) individual / m2. In River Diyala, the highest population density (18046.71),(382649.733) and (9908.00) individual / m2 respectively for mollusks, insects and Oligochaeta. The results also showed that the highest biodiversity values according to Shannon-weaver Index, where appeared in Diyala river was higher from this that recorded in Tigris river , where H value (18.6) and J value(8.29), Tiger river distinguished The lower values (3.31,1.56) each of H,J respectively . Positive and Negative relationships shows between almost invertebrates groups with physical and chemical characteristic of water. Positive significant relationship distinguished with almost all groups with Nitrate NO3 except Crustacea, whereas Negative relations with DO with each of Insects and Mollusks, where pH values Negative relationships with each of Insects and Oligochaeta. Also the relations were Negative to turbidity NTU values with each of Mollusks, Oligochaeta and Crustacea. These Connections may explain the effects of these characteristics on the survival and adaptation of these organisms to the study area.